CHEMICAL CONSTITUENTS AND BIOACTIVITIES OF ESSENTIAL OILS FROM THE GENUS PIPER (PIPERACEAE): A REVIEW - Silva, Minelly Azevedo da; PASSARINI, GUILHERME MATOS; Martinez, Leandro do Nascimento; FACUNDO, VALDIR ALVES; TELES, CAROLINA GARCIA BIONI; Kuehn, Christian Collins (South American Journal of Basic Education, Technical and Technological, 2021)
The essential oils are object of studies that aim the identification of its compounds and its possible biological activities. The present investigation is a literature review of essential oils extracted from species of the Piper genus that presented biological activities. The references selected reports the extraction of oils from different plant parts and its bioactivities. The most reported actions were: antibacterial, antifungal, antioxidant and larvicidal/insecticidal. This review is of great relevance to promote further investigations about the biological effects of volatile compounds present in the essential oils of species belonging to the family Piperaceae, hence contributing for the research on new biotechnological products, such as medicines and pesticides.